Horizontal Ridge Augmentation: A Comparison between Khoury and Urban Technique - Javier Sánchez-Sánchez; Finn Niclas Pickert; Luis Sánchez-Labrador; Francisco GF Tresguerres; José María Martínez-González; Cristina Meniz-García (Biology, 2021)
Purpose. The objective of this systematic review was to evaluate and compare the clinical efficacy of horizontal alveolar ridge augmentation techniques described by Khoury and Urban. Methods. A systematic electronic search in the MEDLINE databases, SCOPUS, WOS, and the Cochrane Central Register of Controlled Trials (CENTRAL) as well as a manual search, were conducted independently by two reviewers up to July 2021. Results. Six studies met the pre-established inclusion criteria and were included in the descriptive analysis. Due to the heterogeneity found across the included studies, meta-analysis could not be performed. Horizontal bone gain was between 3.93 ± 0.9 mm and 5.02 ± 0.8 mm with the Khoury technique and between 3.9 ± 0.9 mm and 5.68 ± 1.42 mm with the Urban technique. Similar complication rates were reported in both groups: infection (7%), in the Khoury technique, and membrane exposure (3.2–13.6%), in the Urban technique, being the most frequent events. Conclusions. Both techniques were found to be effective, in terms of clinical bone gain, for horizontal alveolar ridge gain. Nevertheless, available literature is limited, and there is a lack of comparative studies to better evaluate the results.